Cross-Sectional Survey on Long Term Sequelae of Pediatric COVID-19 among Italian Pediatricians - Giuseppe Fabio Parisi; Lucia Diaferio; Giulia Brindisi; Cristiana Indolfi; Giuseppina Rosaria Umano; Angela Klain; Giuseppe Marchese; Daniele Giovanni Ghiglioni; Anna Maria Zicari; Gian Luigi Marseglia; Michele Miraglia del Giudice (MDPI AG, 2021)
The persistence of symptoms after recovery from Coronavirus 2019 (COVID-19) is defined as long COVID, an entity that had occurred among adults but which is not yet well characterized in pediatric ages. The purpose of this work was to present some of the data from a survey addressed to Italian pediatricians concerning the impact of long-COVID among children who recovered from severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) infection. The questionnaire was designed and pre-tested in February 2021 by a working group of experts from the Italian Pediatric Society for Allergy and Immunology (SIAIP). The survey was emailed once in March 2021 to a sample of Italian pediatricians. A total 267 Italian pediatricians participated in our survey. According to most pediatricians (97.3%), the persistence of symptoms is found in less than 20% of children. Specifically, with regard to the symptoms that persist even after swab negativization, fatigue was the most mentioned one (75.6%). Long-COVID would seem to be a phenomenon of limited occurrence in pediatric ages, affecting less than 20% of children. Among all of the symptoms, the one that was most prevalent was fatigue, a pathological entity that is associated with many viral diseases.